Estratégias de escolarização de homossexuais com sucesso acadêmico - Janice Aparecida de Souza (2013)
The research investigates the impact of sexual orientation on performance and permanence of lesbian and gay students in school spaces. It identifies the strategies adopted by students to enter and remain in the prestigious courses of Law and Medicine of the Federal University of Minas Gerais (UFMG). The methodology adopted, qualitative, comprised two sources of data collection: the first part, the application of one hundred exploratory questionnaires in a Confraternity of homosexuals. The second, semistructured interviews with two lesbians and two gay students of UFMG. We conclude that students were academically successful due to the omission of their sexual orientation, to privileged social and financial condition, and to the posture of the private schools they attended to.